Influences of lightweight foam concrete roof tile hollow sections and thermal reflective coating in cool roof system - Yew, Ming Chian; Saw, Lip Huat; Yeo, Wei Hong; Ho, Mun Ling (Penerbit Universiti Kebangsaan Malaysia, 2023)
Modern civilization is increasing the commercial and residential buildings demand, while a big part of the energy consumed in buildings is for cooling purposes. Modern building design requires sustainable cooling facilities when an excellent roofing system plays an important role. This paper investigates the performance of a cool roofing system that integrates lightweight foam concrete roof tile and a passive cool roofing system. The concrete fabrication process introduced the concrete roof tile hollow sections to improve the roof’s thermal resistance. The densities of the lightweight foam concrete roof tile were varied at 1300 kg/m3 and 1100 kg/m3, respectively, to determine a better performance of roof tile than a basic concrete roof with a density of 2500 kg/m3. Two spotlight lamps that imitated solar irradiation in the afternoon were used as the heat supplied on four roof prototypes. The results showed that the attic temperature dropped from 40.8 °C to 33.5 °C (-7.3 °C) after 60 minutes of heat exposure when the roof was a foam concrete, the roof density was lower, with hollow longitude sections and thermal reflective coating. Furthermore, the average attic temperature increment rate was reduced by 70.2 % when an ideal cool roofing system was applied.